2022
DOI: 10.1080/23273798.2022.2159989
|View full text |Cite
|
Sign up to set email alerts
|

Features matter: the role of number and gender features during the online processing of subject- and object- relative clauses in Italian

Abstract: In this study, we investigated whether different morphosyntactic features, i.e., number and gender, play a role during the adult online comprehension of subject relative clauses (SRC) and object relative clauses (ORC), in Italian. This study was inspired by developmental studies showing that children struggle with ORC compared to SRC; yet, ORC comprehension improves if the head and the subject of the RC mismatch in relevant morphosyntactic features (e.g., number but not gender in Italian, based on the featural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 91 publications
0
6
1
Order By: Relevance
“…The subject-object asymmetry, and the role played by different kinds of grammatical features in modulating such asymmetry, has been experimentally replicated also for adults in a recent study by Biondo et al (2022). Two self-paced reading experiments on Italian, testing the role of feature match/mismatch in both centre-embedded and final relative clauses, consistently found higher reading times for ORCs when compared to SRCs.…”
Section: Structural Constraints and Working Memory Principles: A Meet...mentioning
confidence: 77%
See 2 more Smart Citations
“…The subject-object asymmetry, and the role played by different kinds of grammatical features in modulating such asymmetry, has been experimentally replicated also for adults in a recent study by Biondo et al (2022). Two self-paced reading experiments on Italian, testing the role of feature match/mismatch in both centre-embedded and final relative clauses, consistently found higher reading times for ORCs when compared to SRCs.…”
Section: Structural Constraints and Working Memory Principles: A Meet...mentioning
confidence: 77%
“…One of the most successful frameworks in explaining the asymmetries found across types of relative clauses is the featural Relativized Minimality approach (Rizzi 1990(Rizzi , 2004; further analysed by Grillo 2008;Belletti and Contemori 2009;Friedmann, Belletti and Rizzi 2009;Belletti et al 2012;Biondo et al 2022). This approach is rooted in the Locality Principle, which states that syntactic relations must take place in the smallest possible structural domain, giving rise to a framework which has the explanatory power needed to account for a number of attested phenomena, restating them as intervention effects.…”
Section: Structural Constraints and Working Memory Principles: A Meet...mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 4, the first movement step raises the internal VP argument across the agent. This may give rise to classic intervention effects (Friedmann et al, 2009) that have been documented in both adults and children (for an overview, see Biondo et al, 2022). This line of reasoning was initially proposed by Zesiger et al (2010) for French and more recently by Arosio and Giustolisi (2019) for Italian.…”
Section: Introductionmentioning
confidence: 99%
“…In object relative clauses, the object is moved across the subject, similarly to the movement step shown in (4). This factor has been thought to account for the higher processing load in both children (e.g., Adani, 2011; Arosio et al, 2009) and adults (e.g., Gordon et al, 2001; Grodner and Gibson, 2005; King and Just, 1991; Staub, 2010; Staub et al, 2017; Traxler et al, 2002, Biondo et al 2022), also considering the involvement of memory resources in maintaining active long-distance dependencies (Gibson 2000; Lewis and Vasisht 2005). The results presented in Arosio et al (2011) showed a clear correlation between digit span and object relatives, i.e., the constructions with higher complexity.…”
Section: Introductionmentioning
confidence: 99%